What's on your hard drive?. - Maurer, Jim (New York ACM, 2005)
Welcome back for another installment of "What's on Your Hard Drive?" where you tell us about the tools you love, the tools you hate, and a category that's recently grown in popularity: tools that you both love and hate. And by tools we don't just mean pieces of software; feel free to express your love and/or hatred for both IDEs and the programming languages we use within them. Programming language allegiances are usually much stronger than tool preferences, so this is bound to make for some heated debate over at www.acmqueue.com, where you can both submit to WOYHD and comment on others' submissions.
Keywords: General Literature; Miscellaneous; Hardware; Memory structures; Design styles; Mass storage (e.g. magnetic, optical, RAID).; Computing Milieux; Personal computing; Hardware; Management/Maintenance.